Flotation study of fine grained carbonaceous sedimentary apatite ore – Challenges in process mineralogy and impact of hydrodynamics. (1st June 2018) - Hoang, Duong Huu; Kupka, Nathalie; Peuker, Urs Alexander; Rudolph, Martin
Abstract: The flotation beneficiation of apatite for phosphate production is challenging for finely disseminated sedimentary ores rich in carbonates. Similarities in surface properties of the semi-soluble salt-type carbonate and phosphate calcium minerals combined with fine intergrowth are the main reasons for poor grade and low recoveries. Imperfect depression of the calcium/magnesium carbonate minerals, e.g. calcite and dolomite, will lead to weak hydrophobic surface properties and thus true flotation of this gangue. Furthermore, fine particles, even though sufficiently liberated, strongly affect the bubble-particle collection due to negative rheological effects within the pulp leading to a drop in flotation kinetics of the fine valuables and an increase in entrainment of fine gangue particles. This study presents the results and discussions based on automated mineralogy (conducted with a Mineral Liberation Analyzer – MLA) of size-by-size-by-liberation analyses for various mineral groups. In addition, results on different turbulent hydrodynamic parameters are presented based on various tests in a lab cell.